Prep1, A Homeodomain Transcription Factor Involved in Glucose and Lipid Metabolism - Oriente, Francesco; Perruolo, Giuseppe; Cimmino, Ilaria; Cabaro, Serena; Liotti, Antonietta; Longo, Michele; Miele, Claudia; Formisano, Pietro; Beguinot, Francesco (Frontiers in Endocrinology, 2018)
The three-amino acid loop extension (TALE ) homeodomain proteins are a family of transcription factor including the mammalian Pbx, MEIS and Prep proteins. TALE proteins can bind other transcription factors such as Pdx-1 and play an important role in the regulation of glucose metabolism. Experiments performed in mutant mice have shown that while the single Pbx1 or Pdx-1 knockout mice feature pancreatic islet malformations, impaired glucose tolerance and hypoinsulinemia, the trans-heterozygous Pbx1+/- Pdx1+/- mice develop age-dependent overt diabetes mellitus. In contrast, Prep1 plays a different role with respect to these proteins. Indeed, Prep1 hypomorphic mice, expressing low levels of protein, feature pancreatic islet hypoplasia accompanied by hypoinsulinemia similar to Pbx1 or Pdx1. Nevertheless, these animals show increased insulin sensitivity in skeletal muscle, liver and adipose tissue accompanied by protection from streptozotocin-induced diabetes. In addition, Prep1 hypomorphic mice feature reduced triglyceride synthesis and do not develop steatohepatitis after a methionine and coline deficient diet. In this review we have underlined how important metabolic functions are controlled by TALE proteins, in particular by Prep1, leading to hypothesis that its suppression might represent beneficial effect in the care of metabolic diseases.